Nigerian women's modern contraceptive use: evidence from NDHS 2018 - Ibrahim Banaru Abubakar; Hafsat Banaru Abubakar (Bioscientifica, 2024)
Nigeria has the largest population in Africa, a high fertility rate, and unmet needs for family planning. Family planning is a key strategy for sustainable development. A good knowledge of factors that determine contraceptive uptake is imperative for policy formulation. A nationally representative secondary dataset of 41,821 women aged 15-49 years who participated in the 2018 Nigeria Demographic and Health Survey was analyzed. Multivariate logistic regression was used to examine the association between various factors and the current use of modern contraceptives. The respondents' average age was 35.9 ± 7.9 years. Overall, contraceptive prevalence was 16.6% for traditional methods and 12.2% for modern methods. Predictors of an increase in modern contraception use were age 40-44 (aOR = 1.07, 95% CI: 0.75-1.53); being a working-class woman (aOR = 1.15, 95% CI: 0.99-1.33); living in an urban area (aOR = 1.14, 95% CI: 0.97-1.33); living in the South West (aOR = 1.36, 95% CI: 1.03-1.79); increasing wealth (aOR = 0.78, 95% CI: 0.66-0.93); and health insurance (aOR = 1.22, 95% CI: 0.89-1.68). Couple dynamics influencing modern contraceptive use were joint decision (aOR = 2.16, 95% CI: 1.81-2.59), self-decision on health care (aOR = 1.34, 95% CI: 1.06-1.70), and earning more than a partner (aOR = 1.14, 95% CI: 0.78-1.66). There are significant variations in contraceptive uptake attributable to socioeconomic and political inequalities, requiring a holistic approach to mitigate barriers and improve contraceptive uptake.